WELL OPTIMIZATION ON XA-2 AND XA-S INTEGRATED WITH THE SURFACE AND SUBSURFACE IN THE X GAS FIELD - WAHYUDI (NIM : 22209061), AGUS
X gas field producing gas from retrograde gas reservoir, has less than 15 years remaining contract to be completed with rate constraints. Three years from now, plateau rate has to be reached at 61 MMSCFD for whole field and after that rate over 15 MMSCFD as an economic limit has to be reached. Material Balance analysis X field showed that X field optimization is needed to fulfill the contract that has been set. The purpose of this study is to perform well optimization on XA-2 and XA-S integrated with the surface and subsurface on X field and arrange the optimization scenario. Scenario to determine the optimum parameters in the production system so that the oil recovery factor obtained the greatest, and to know the large increase in oil recovery factor after optimization of the production system This study is started by making a reservoir model using the material balance analysis to determine the potentials which are still available. After that, it is followed by matching Vertical Lift Performance (VLP) process to gain well head pressure data and correct well hole parameters. After the results were used for VLP process making the overall scheme of the surface fascilities and integrated, well below the surface or surfaces by taking into account current condition. The simulation results show the opening of the Well XA-S and the decrease of 5030 separator pressure on the X field managed to increase the value gas recovery factor from 78.85 % to 87.64 %. By considering the average flow rate of 15 MMSCFD of the contract, it is a necessary to restrict the field XA flow rate in accordance with the contract so that the recovery factor obtained of 87.49 %.